Urgensi Akreditasi dalam Sistem Persekolahan: Telaah Konseptual tentang Tujuan, Manfaat, dan Fungsi - Ulya Ulfah; Raihanah; Husnul Yaqin; Hilmi Mizani (Sinergi : Jurnal Ilmiah Multidisiplin, 2026)
Accreditation is a strategic instrument in the school system that serves to guarantee and control the quality of education nationally. This article aims to conceptually examine the urgency of accreditation in the school system by examining its basic concepts, objectives, benefits, and functions. The research employed a library research approach with qualitative-descriptive methods. Data were obtained from laws and regulations, specifically Law Number 20 of 2003 concerning the National Education System, accreditation policies and guidelines issued by the National Accreditation Board for Schools/Madrasahs (BAN-S/M), and scientific literature related to education quality assurance systems. The analysis was conducted using content analysis techniques to synthesize various relevant concepts and regulations. The study results indicate that accreditation is a systematic and comprehensive assessment process of the eligibility and performance of educational units, resulting in a ranking (A, B, C, or not accredited). Conceptually, accreditation aims to provide an overview of school performance and ensure the eligibility of educational services. Its benefits are felt by various stakeholders, from schools, principals, teachers, the community, and the government, serving as a basis for guidance, development, and policymaking. Functionally, accreditation serves as a means of knowledge, public accountability, and continuous quality development and improvement. The implementation of the performance-based Educational Unit Accreditation Instrument (IASP 2020) emphasizes a paradigm shift from compliance-based to performance-based, thus increasingly orienting accreditation toward the quality of learning processes and outcomes. Thus,accreditation is a strategic instrument in strengthening the national education quality assurance system.